RENDEMEN EMPULUR SAGU (Metroxylon sagu Rottb) DARI KAWASAN HUTAN SAGU KAINUI KABUPATEN YAPEN PROPINSI PAPUA BARAT - Batseba Alfonsina Suripatty (JURNAL HUTAN PULAU-PULAU KECIL, 2017)
Sago (Metroxylon sago Rottb) is one of the native plants of Indonesia producing carbohydrate which is quite high compared with other carbohydrate-producing plants. The study used the treatment of the division of sago stems divided into 3 parts, namely the base, the middle and the tip, then each piece of skinned and in the scar as pith and weighed. The pith of each piece of sago stalk is separated then in the ramas to get the starch and the sago pulp. The pith, the dregs and the starch are then weighed per part of the tree trunk. This study aims to determine the weight of pith, dregs and weight of sago starch from several varieties. The results showed that sago varieties studied had the highest amount of flour, respectively, in sago varieties of anangga, kurai varieties, wimir varieties, anaggemo varieties and makbom varieties. As for the production of flour is most abundant in the middle of the sago tree for the five varieties of sago.